UPLC-MS based metabolite profiles of two major bioactive components in herb pair scutellaria–coptis metabolized by intestinal bacteria derived from healthy rats and rats with type 2 diabetes. Issue 13 (12th June 2015) - Du, Le-yue; Qian, Da-wei; Shang, Er-xin; Jiang, Shu; Liu, Pei; Guo, Jian-ming; Su, Shu-lan; Duan, Jin-ao; Xu, Jun; Zhao, Min
Abstract : This study describes the metabolites of two components in scutellaria–coptis metabolized by intestinal bacterial of healthy rats and type 2 diabetic rats. Abstract : Radix Scutellariae ( Scutellaria baicalensis Georgi) and Rhizoma Coptidis ( Coptis chinensis Franch) are widely used in couple to treat type 2 diabetes mellitus in China. Recently, the gut microflora has emerged as another parameter of the pathophysiology of type 2 diabetes mellitus. However, the interaction between this herb couple and the gut microbiome remains unknown. In this research, a rapid, reliable and automated analysis method, ultra-performance liquid chromatography/quadrupole-time-of-flight mass spectrometry (UPLC-Q-TOF/MS) technique, combined with Metabolynx™ software, was applied for the identification of the metabolites of the main bioactive components in scutellaria–coptis extract by intestinal bacteria from normal and type 2 diabetic rat feces. The data indicated that type 2 diabetic rat intestinal flora could generate a great number of baicalein (M2), the aglycone of baicalin, compared with normal samples. In addition, the intestinal flora of normal rats could also produce several conjugates such as hydrogenated baicalin (M1), sulfated berberine (M4), and glucuronidated berberine (M5), while the intestinal flora derived from type 2 diabetic rats could engender oroxylin A (M3) and methylated berberine (M6). The results will be helpful for the further pharmacokinetic study of scutellaria–coptis extract in vivo and also offer value in unravelling how this herb couple works in the treatment of diabetes.